2023
DOI: 10.1177/23337214231176698
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the COVID-19 Pandemic on the Self-Perceived Change of Caregivers’ Burden in Providing Care for People With Dementia

Apichaya Wongmek,
Titima Wongviriyawong,
Sutisa Pitiyarn
et al.

Abstract: Objectives: To explore how the COVID-19 pandemic affects caregiver (CG) burden, the quality of care provided to people with dementia (PwD) and their perceived changes between before and during the pandemic. Methods: A cross-sectional study surveyed primary CGs about burden and self-perceived change in multidimensional domains and compared these before and during the pandemic. Results: About 135 primary CGs of PwD were enrolled at Siriraj Hospital’s Geriatric Clinic in Thailand and assessed using various online… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 42 publications
(58 reference statements)
0
1
0
Order By: Relevance
“…People living with dementia are at high risk of depression, isolation, and behavioral changes, which may have been exacerbated by the COVID‐19 pandemic (Nakanishi et al., 2023 ). Prior studies have demonstrated that caregiver burden increased during the pandemic among informal caregivers of patients with PD (Hattori et al., 2023 ; Suzuki et al., 2021 ) and dementia in studies in India (Mukherjee et al., 2022 ), Thailand (Wongmek et al., 2023 ), Hong Kong (Fong et al., 2021 ), and across the United States (Mitchell et al., 2023 ; Yan et al., 2023 ). Caregiver burden increased in many regions of the world due to factors including aggravation of patient's symptoms, increased stress and anxiety, and needing to spend more hours at home given patients were less able to go out of the home during the pandemic (Carbone et al., 2021 ; Hattori et al., 2023 ).…”
Section: Introductionmentioning
confidence: 99%
“…People living with dementia are at high risk of depression, isolation, and behavioral changes, which may have been exacerbated by the COVID‐19 pandemic (Nakanishi et al., 2023 ). Prior studies have demonstrated that caregiver burden increased during the pandemic among informal caregivers of patients with PD (Hattori et al., 2023 ; Suzuki et al., 2021 ) and dementia in studies in India (Mukherjee et al., 2022 ), Thailand (Wongmek et al., 2023 ), Hong Kong (Fong et al., 2021 ), and across the United States (Mitchell et al., 2023 ; Yan et al., 2023 ). Caregiver burden increased in many regions of the world due to factors including aggravation of patient's symptoms, increased stress and anxiety, and needing to spend more hours at home given patients were less able to go out of the home during the pandemic (Carbone et al., 2021 ; Hattori et al., 2023 ).…”
Section: Introductionmentioning
confidence: 99%